Historical Jesus: A Multidisciplinary Perspective and the Aesthetics in Western Images of the Sacred - Silva Lourenço, Hudson (2025)
This article examines the discrepancy between the historical Jesus and his representations in Western art, aesthetically transformed to reflect European features. Drawing on the analyses of John P. Meier and historical-critical studies by Antonio Piñero, Fernando Bermejo Rubio, and others, we discuss the ideological role of these images in reinforcing Eurocentric hegemony. Supported by philosophical aesthetics, we argue for the need to reassess these representations within a religious context as well, promoting an inclusive and historically accurate aesthetic that better reflects cultural diversity and provides a meaningful image of Jesus for marginalized communities.